A contribuição do Assistente Social para a permanência dos estudantes nos Cursos Técnicos Integrados ao Ensino Médio no Instituto Federal do Paraná - IFPR - Ferreira, Jéssica Fernanda Wessler (2020)
The expansion of the Federal Network of Professional, Scientific and Technological Education contributed to the working class’ access to higher education institutions and, with the creation of the Federal Institutes of Education (IFs), in 2008, the access to Technical Courses of Medium level expanded. With the access of the working class to Higher Education and Professional Education, the concern arose about their permanence in the Federal Network, in order to meet their subsistence demands. The PNAES (2010) aimed, therefore, to expand the conditions for the permanence of the students, being also the main responsible for the insertion of the Social Work Assistant in the field of Federal Education. In this way, this dissertation investigates what are the challenges and the possibilities of the work of the Social Work Assistant in relation to the permanence of the students of the Technical Courses Integrated to the High School of the IFPR. The research, with a qualitative approach, counted with the participation of 10 Social work Assistants, who work in the IFPR Campuses. The research’s problem was: to what extent do the dimensions of the Social Work Assistant's performance, based on the actions of Student Assistance, contribute to the permanence of students in the IFPR's Technical courses Integrated to High School? The specific objectives were: a) Historicizing the profession of Social Work, having as reference the structural crisis of the capital, the Neoliberal Policies and the Social Policies / Educational Policies; b) Analyze the possibilities and challenges related to the development of the actions of Social work Assistants aiming to the permanence of students in Technical Courses integrated to High School at the Federal Institute of Paraná - IFPR. It was possible to infer, through the results of the research, that the Social Work Assistants, based on their competences and attributions guided by the ethical-political principles of the profession, contribute to the permanence of students in the Technical Courses Integrated to High School of IFPR, through the orientation of students and their families and the promotion of study spaces about the access to social policies.